Integrating forest windthrow assessment data in the process of windscape reconstruction: Case of the extratropical storms downscaled for the Gutai Mountains (Romania) - Ilies, Gabriela; Ilies, Marin; Hotea, Mihai; Bumbak, Silviu-Vasile; Hodor, Nicolaie; Ilies, Dorina-Camelia; Caciora, Tudor; Safarov, Bahordihon; Morar, Cezar; Valjarević, Aleksandar; Berdenov, Zharas; Lukić, Tin; et al. (Frontiers in Environmental Science, 2022)
Downscaling and modelling natural disturbances such as the extratropical storms is important for understanding and predicting the behaviour of the air-flow over complex forested areas, especially in high-wind instances that generate damages. Therefore, the rationale of the research was that the windscape of a storm could be reconstructed based on the features of consequent forest windthrows. Main input data for the model was derived from data on forest damages (extension, orientation and depth of windthrows) retrieved from combined UAV imagery, high resolution imagery and field survey, integrated with terrain, wind data at stations within the study area, landcover, overturning and breaking point conditions for tree species, and human interventions. Using a GIS environment, a critical wind speed index was calculated as well as the main wind direction on each damaged stand, considering the factors that lead to windthrows. This model was then compared to a computational fluid dynamics wind model built with WindNinja app, using the conservation of mass and momentum solver, at the moment of the storm, and adjusted. Ultimately, maps and 3D models were presented to the main stakeholders in the area: forest management, protected area operatives, road and tourist infrastructures’ management in order to enhance the resilience strategies and environmental protection.